2019
DOI: 10.1186/s12864-019-5455-1
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and expression analysis of expansin gene family in common wheat (Triticum aestivum L.)

Abstract: BackgroundExpansin loosens plant cell walls and involves in cell enlargement and various abiotic stresses. Plant expansin superfamily contains four subfamilies: α-expansin (EXPA), β-expansin (EXPB), expansin-like A (EXLA), and expansin-like B (EXLB). In this work, we performed a comprehensive study on the molecular characterization, phylogenetic relationship and expression profiling of common wheat (Triticum aestivum) expansin gene family using the recently released wheat genome database (IWGSC RefSeq v1.1 wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 97 publications
6
66
0
Order By: Relevance
“…Multiple sequence alignment of the amino acid sequences of Dof proteins were performed based on MUSCLE program (http://www.ebi.ac.uk/Tools/msa/ muscle/) [75,76]. Subsequently, the Bayesian and N-J phylogenetic trees were constructed based on the method by Han et al [77]. Furthermore, maximum likelihood and minimal evolution methods were applied for the tree construction to validate the results of the N-J method in MEGA5.0.…”
Section: Phylogenetic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple sequence alignment of the amino acid sequences of Dof proteins were performed based on MUSCLE program (http://www.ebi.ac.uk/Tools/msa/ muscle/) [75,76]. Subsequently, the Bayesian and N-J phylogenetic trees were constructed based on the method by Han et al [77]. Furthermore, maximum likelihood and minimal evolution methods were applied for the tree construction to validate the results of the N-J method in MEGA5.0.…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…The Chinese wheat cultivar Zhongmai 175 seedlings were cultivated into two leaves and one heart stage according to the culture conditions of Han et al [77]. Then seedlings were treated with the following conditions: heavy metal stress with 300 μM CrCl 3 and CdCl 2 , drought stress with 20% (w/v) PEG 6000, salinity stress with 200 mM NaCl, oxidative stress with 15 mM H 2 O 2 , hormone stress with 100 μM ABA (abscisic acid) and SA (salicylic acid), and 10 μM IAA (indole-3-acetic acid), cold stress under 4°C) and heat stress under 42°C.…”
Section: Plant Materials and Abiotic Stress Treatmentsmentioning
confidence: 99%
“…In the pathway of extracellular region (Fig. 10c), expansin gene family can increase the extensibility of cell wall [41][42][43]. Previous studies have shown that overexpression of expansin family members can cause the changes in crop morphology and improve the crop adaptability of stress resistance or low nutrition conditions [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…The Chinese wheat cultivar Zhongmai 175 seedlings were cultivated into two leaves and one heart stage according to the culture conditions of Han et al [77]. Then seedlings were treated with the…”
Section: Plant Materials and Abiotic Stress Treatmentsmentioning
confidence: 99%